Classifying two-dimensional hyporeductive triple algebra - A. Nourou Issa (International Journal of Mathematics and Mathematical Sciences)
Two-dimensional real hyporeductive triple algebras (h.t.a.) are investigated. A classification of such algebras is presented. As a consequence, a classification of two-dimensional real Lie triple algebras (i.e., generalized Lie triple systems) and two-dimensional real Bol algebras is given .